Efforts to Improve Learning Quality through Comic Making Training - Perpetue, Okoua Beatrice (Community Service Akseprin Journal, 2023)
Teaching materials as factors that influence the teaching and learning process run effectively and efficiently. Based on the results of preliminary analysis, almost all teachers have never developed their own teaching materials. In addition, fractions are a topic that is considered difficult by most students, especially if presented in the form of story problems. There needs to be an innovation of teaching materials that are in accordance with students' cognitive levels, increase interest in reading, and accommodate students' numeracy literacy skills. One of the efforts that can be done is to provide training in teaching materials in the form of fractional comics. Comics are a reading genre that students relatively like, have interesting storylines, colorful images and contain a sense of humor. The comic making training was attended by 10 teachers from several schools. The implementation of training and mentoring began on July 31, 2021 to August 12, 2021, carried out in stages as many as four meetings with lecture and practice methods. From the results of service activities, teachers' ability to make teaching materials in the form of fractional comics increased both in knowledge and technique. Some indicators of success in this training include teachers having comprehension competence in making comic teaching materials and being able to make comics starting from determining characters to preparing panels to sketch images. Thus, comic teaching materials that have been successfully compiled can then be used by students to get the benefits